Screws Fixation for Oblique Lateral Lumbar Interbody Fusion (OL-LIF): A Finite Element Study. (17th May 2021) - Ling, Qinjie; Zhang, Huanliang; He, Erxing
Abstract : Background . The combination of screw fixation and cage can provide stability in lumbar interbody fusion (LIF), which is an important technique to treat lumbar degeneration diseases. As the narrow surface cage is developed in oblique lateral lumbar interbody fusion (OL-LIF), screw fixation should be improved at the same time. We used the finite element (FE) method to investigate the biomechanics response by three different ways of screw fixation in OL-LIF. Methods . Using a validated FE model, OL-LIF with 3 different screw fixations was simulated, including percutaneous transverterbral screw (PTVS) fixation, percutaneous cortical bone trajectory screw (PCBTS) fixation, and percutaneous transpedical screw (PPS) fixation. Range of motion (ROM), vertebral body displacement, cage displacement, cage stress, cortical bone stress, and screw stress were compared. Results . ROM in FE models significantly decreased by 84-89% in flexion, 91-93% in extension, 78-89% in right and left lateral bending, and 73-82% in right and left axial rotation compared to the original model. The maximum displacement of the vertebral body and the cage in six motions except for the extension of model PTVS was the smallest among models. Meanwhile, the model PTVS had the higher stress of screw-rods system and also the lowest stress of cage. In all moments, the maximum stresses of the cages were lower than their yield stress. Conclusions . Three screw fixations can highly restrict the surgical functional spinal unit (FSU). PTVS provided the better stability than the other two screw fixations. It may be a good choice for OL-LIF.